Content Analysis of Sustainability Report in Indonesia’s Banking Sector - Azizah, Muthia; Widiyati, Dian (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Sustainability reporting is considered as one of the strategic tools for companies in order to demonstrate their environmental, social, and governance (ESG) responsibilities. In the banking sector, sustainability reports play an important role in complying with regulations and increasing transparency to stakeholders. The aim of this study is to analyze the completeness of sustainability report disclosures based on the 2021 Global Reporting Initiative (GRI) standards and compare the level of disclosure between banks based on the 2023 Asia Sustainability Reporting Rating (ASRRAT). The study used a content analysis method with a sample of seven banks from various categories of Bank Groups Based on Core Capital (KBMI). The results of the study show that all banks have followed the 2021 GRI standards, although there are variations in the completeness of disclosures on economic, environmental, and social aspects. In addition, banks with a Platinum rating have better disclosures than those with a Gold rating; especially, on the GRI standards for the financial services sector. This study provides a contribution in the form of policy suggestions for the Financial Services Authority (OJK) in order to improve supervision of sustainability reporting and align with international standards. Meanwhile, for banks, it is important to strengthen disclosures on material topics; such as, anti-competitive behavior and tax transparency, to improve the quality of reports and build stakeholder trust.